2005
DOI: 10.2214/ajr.184.4.01841199
|View full text |Cite
|
Sign up to set email alerts
|

Value of FDG PET in the Assessment of Patients with Multiple Myeloma

Abstract: FDG PET is able to detect bone marrow involvement in patients with multiple myeloma. FDG PET is useful in assessing extent of disease at time of initial diagnosis, contributing to staging that is more accurate. FDG PET is also useful for evaluating therapy response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(137 citation statements)
references
References 23 publications
3
129
0
5
Order By: Relevance
“…The studies with a methodological quality above average were the studies by Bredella et al, 10 Fonti et al, 14 Hur et al, 16,17 Schirrmeister et al, 23,24 and Zamagni et al 4,21 Comparison of 18 FDG PET or PET-CT and Conventional Imaging at Staging Of the 18 studies conducted, concordance assessment between WBXR and 18 FDG PET scan was possible in 7 (concerning 242 patients). In 6 out of these 7 studies, 18 FDG PET (with or without CT) scan showed more lytic lesions then conventional WBXR with the exception of lytic lesions located in the skull 4,[9][10][11]19,21,23,24 (Table 5). Two studies compared 18 FDG PET-CT scan with WBXR.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies with a methodological quality above average were the studies by Bredella et al, 10 Fonti et al, 14 Hur et al, 16,17 Schirrmeister et al, 23,24 and Zamagni et al 4,21 Comparison of 18 FDG PET or PET-CT and Conventional Imaging at Staging Of the 18 studies conducted, concordance assessment between WBXR and 18 FDG PET scan was possible in 7 (concerning 242 patients). In 6 out of these 7 studies, 18 FDG PET (with or without CT) scan showed more lytic lesions then conventional WBXR with the exception of lytic lesions located in the skull 4,[9][10][11]19,21,23,24 (Table 5). Two studies compared 18 FDG PET-CT scan with WBXR.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
“…Finally, 18 studies involving 798 patients were included in this systematic review (Figure 1). 3,4,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] There was no disagreement between the reviewers regarding the inclusion of the articles. The characteristics of the included studies are presented in Table 2.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, several myeloma organizations and institutions have suggested that wholebody LDCT should replace conventional radiography for the work-up of patients with MM because of the higher sensitivity for the detection of osteolytic lesions [3] . In addition, numerous studies have shown that FDG PET/ CT is more sensitive in the detection of osteolytic lesions in MM compared to whole-body X-ray [7,8,16] . Based on a systematic review from 2012 involving 18 studies and 798 patients, FDG PET/CT was able to detect MM osteolytic lesions with a sensitivity of approximately 80%-90% and a specificity of 80%-100% [14,17] .…”
Section: Discussionmentioning
confidence: 99%